Features of physical development, physical preparedness and functional state of boys and girls – students of Polish higher educational establishments - Krzysztof Prusik; Katarzyna Prusik; Zh.L. Kozina; S.S. Iermakov (Physical Education of Students, 2013)
The features of level and structure of indexes of physical development, physical preparedness and functional state of students are considered. In research 50 took part students of Higher School of Sciences about health from Bydgoshch (14 boys and 36 girls, age 18-29 years). Reliable distinctions are exposed in physical preparedness and functional state of boys and girls on the indexes of force. Indexes of psychophysiological possibilities, frequencies of heart-throbs in a state of rest, the index of Ruf'e have no reliable distinctions at boys and girls. It is shown that power capabilities have the most value in complex preparedness of boys. Functional and psychophysiological possibilities have the most value in complex preparedness of girls. The factor structure of preparedness of girls is differ by greater complication as compared to boys. On the level of physical preparedness and functional state of girls in a greater degree of anthropometric information have influence as compared to boys. Power capabilities for girls occupy middle position in the general structure of preparedness, while for boys' power capabilities occupy leading position. It is shown that on employments on physical education of boys it is necessary to do an accent on development of force, while for girls - on development of endurance (functional possibilities) and in a greater degree as compared to boys it is necessary to take into account psychophysiological possibilities.